Challenges for the colombian central government in post-agreement financing (Revista científica Pensamiento y Gestión, 2020)
This paper analyzes the difficulties in raising tax revenue for the central government in a post-agreement era. Through an analysis of main components and stylized facts it is found that there are not enough monetary resources available to implement the peace agreement. This may result inan incomplete implementation of the agreement and a revision of public spending in education, pension system, health system, rural economy, debt service, transport infrastructure and strengthening the DIAN to increase and redistribute the tax burden.